2000
DOI: 10.1093/condor/102.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Survival, Emigration, and Winter Population Structure of Harlequin Ducks

Abstract: A population of individually marked Harlequin Ducks (Histrionicus histrionicus) at White Rock, British Columbia, Canada was examined to measure the degree of population differentiation among birds which pair during the winter months. This required an understanding of the patterns of emigration among wintering sites in different segments of the population. Some juveniles arrived at the wintering grounds accompanied by their mothers, thus initially arriving into the same winter population as their parents. Young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 26 publications
2
19
1
Order By: Relevance
“…The local mortality rate of adult males was estimated at ca. 18% at White Rock, British Columbia, from 1994 to 1999 (Cooke et al 2000). There are four possible explanations for the apparently low proportions: 1) immature males misidentified as females, 2) high proportions of immatures in other locations where we did not survey, 3) local adult survival rates in the literature are underestimated, or 4) the proportions are real and the population is declining.…”
Section: Discussionmentioning
confidence: 89%
“…The local mortality rate of adult males was estimated at ca. 18% at White Rock, British Columbia, from 1994 to 1999 (Cooke et al 2000). There are four possible explanations for the apparently low proportions: 1) immature males misidentified as females, 2) high proportions of immatures in other locations where we did not survey, 3) local adult survival rates in the literature are underestimated, or 4) the proportions are real and the population is declining.…”
Section: Discussionmentioning
confidence: 89%
“…Results suggested that sampling areas were largely homogeneous for both types of genetic markers, although slightly higher levels of differentiation were observed between more distant regions using mtDNA. This result was surprising as Cooke et al (2000) observed adult Harlequin Ducks to exhibit high levels of site fidelity to molting and wintering areas of coastal British Columbia, which they suggested could lead to genetic differentiation of wintering aggregations if mate choice occurs in these locations. Following many years of intensive study, Iverson et al (2004) were able to quantify betweenyear rates of adult molt-site fidelity of Harlequin Ducks in Prince William Sound, Alaska via the homing rate.…”
Section: Demografía Genética Y El Valor De Los Mensajes Confusosmentioning
confidence: 93%
“…We studied Harlequin Duck habitat associations in Prince William Sound during winter to identify environmental variables that relate to Harlequin Duck densities and to assess the status of Harlequin Duck populations following the Exxon Valdez oil spill. Evaluation of Harlequin Duck population recovery from the oil spill has been constrained by a paucity of prespill data from winter, the season of highest abundance of Harlequin Ducks in Prince William Sound and likely the period of formation of core subpopulations from a population structure perspective (Cooke et al 2000). For this study, we adopted a control-impact study design to assess potential oil spill effects, in which we compared densities of Harlequin Ducks between oiled and unoiled areas, recognizing the need to control for intrinsic area differences (Wiens and Parker 1995).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of data suggests that Harlequin Ducks exhibit high philopatry throughout their annual cycle (Cooke et al 2000. Harlequin Duck winter habitat use is likely influenced by strong philopatry (Cooke et al 2000), which reflects high stability of nearshore environments coupled with advantages of philopatry, including site familiarity and interannual pair reunion Cooke 1999, Smith et al 2000).…”
Section: Significance Of Philopatrymentioning
confidence: 99%